Antimicrobial usage in smallholder poultry production in Nigeria - Bamidele, Oladeji; Amole, Tunde A.; Oyewale, A.O.; Bamidele, O.O.; Yakubu, A.; Ogundu, E.U.; Ajayi, O.F.; Hassan, A.W. (Hindawi Limited, 2022)
The indiscriminate use of antimicrobials in livestock production is of increasing concern due to the threat of antimicrobial resistance in both humans and animals. Much emphasis has been placed on intensively managed poultry production systems, which routinely use antimicrobials as against smallholder poultry production systems (SPPS). Therefore, this study investigated the use of antimicrobials among smallholder poultry farmers in Nigeria, and compared the prevalence of antimicrobial drug use against the practice of ethnoveterinary medicine (EVM). A cross-sectional study was conducted in five states (agroecologies) of Nigeria using structured questionnaires administered on a total of 350 farmers. The practice of EVM was prevalent among most of the farmers (39%). The western method (pharmaceuticals) was practiced by a large proportion of farmers (60%), either solely (25%) or in combination with EVM (35%). Antimicrobials were used primarily for treatment and prevention of diseases (78%). Semi-scavenging system of production had the highest proportion (49%) of farmers using antimicrobials, compared to semi-intensive (37%) and scavenging (14%) systems. Gender (χ2 = 9.30, p = 0.01), and location (χ2 = 216.86, p ≤ 0.001), influenced farmers’ choice of methods for bird treatment. Education (odds ratio [OR] odds ratio [OR] 3.06, 95% CI 2.10–4.44), income (OR 1.99, 95% CI 1.10–3.59) and management system (OR 1.97, CI% 1.1–3.45) were most associated with antimicrobial use. Critically important antibiotics, with lower to higher risk of antimicrobial resistance, were used by farmers (40%). These findings showed the indiscriminate use of antimicrobials by farmers and the potential risk of antimicrobial resistance within the SPPS in Nigeria.